Individual, relational and institutional dimensions of resilience of beginning teachers graduated from a public university - Paula Verónica Villalobos Vergara; Universidad de Santiago de Chile; Jenny Assael Budnik; Universidad de Chile (Escuela de Psicología, Pontificia Universidad Católica de Valparaíso, 2018)
Starting from the need to understand the conditions that allow teachers to overcome the daily challenges related to their own job and remain committed to teaching, we resort to the concept of teacher resilience, in a research with beginning teachers, which purpose is to understand the individual, relational and institutional dimensions that nurture teacher resilience on novice teachers graduated from a Chilean public university. For these purposes, it was carried out a qualitative exploratory research that consisted of semi-structured interviews with seven teachers of primary and secondary education, every one of which was analyzed under the guidelines of grounded theory. At an individual level, the results denote the importance related to the willingness to learn and also to the development of teaching skills; at a relational level is evident the importance of positive relationships with the leadership, peers, students and family; at an institutional level, it is evident the importance of providing professional autonomy and support from a multidisciplinary team that would help to lead the teachers' daily work with the students.